PHAGE FORMATION IN STAPHYLOCOCCUS MUSCAE CULTURES : X. THE RELATIONSHIP BETWEEN VIRUS SYNTHESIS, THE RELEASE OF BACTERIAL RIBONUCLEIC ACID, VIRUS LIBERATION, AND CELLULAR LYSIS - Price, Winston H. (The Rockefeller University Press, 1952)
1. Under a variety of conditions in which cells are infected with one or a few virus particles and the host cells are killed, but no infective particles or virus material is formed as indicated by plaque count, one-step growth curve, or protein or desoxyribonucleic determinations, the cells neither lyse nor release ribonucleic acid into the medium. 2. The "killing" effect of S. muscae phage is separate from its lytic property. 3. The release of ribonucleic acid into the medium is not simply due to the killing of the cell by the virus, and ribonucleic acid is never found in the medium unless virus material is synthesized. 4. Infected cells of S. muscae synthesizing virus release ribonucleic acid into the medium before cellular lysis begins and before any virus is liberated. 5. The higher the phage yield the more ribonucleic acid is released into the medium before any virus is released. 6. Phage may be released from one strain of Staphylococcus muscae without cellular lysis, although bacterial lysis begins shortly after the virus is released. In another strain, infected under similar conditions, virus liberation occurs simultaneously with cellular lysis. 7. The viruses liberated from both bacterial strains appear to be the same in so far as they cannot be distinguished by serological tests, have the same plaque type and plaque size, and need the same amino acids added to the medium in order to grow. Furthermore, the virus liberated from one strain can infect and multiply in the other strain and vice versa. 8. It is suggested that virus synthesis, in S. muscae cells infected with one or a few phage particles, leads to a disturbance of the normal cellular metabolism, resulting in lysis of the host cell.